Análise de parâmetros microbiológicos e bioquímicos do solo em sucessão de culturas sob diferentes doses de calcário dolomítico em superfície - Betti, Cristiane Severgnini (2023)
Soil correction with limestone allows for an increase in pH, supply of calcium and magnesium, increased availability of nutrients, reduction of aluminum toxicity, providing better growth conditions for plants and greater productivity. In agricultural systems with crop succession and no-tillage, therefore without soil disturbance, limestone is applied on the surface, initially correcting the surface layer of the soil, creating a correction front due to channels of dead roots in the soil, presence of organic matter, and precipitation. In systems with surface liming, it has been reported in the literature that high doses do not reach the base saturation calculated by the Base Saturation Method. There are responses in productivity for application and doses higher than those commonly used. In the soil system, biochemical parameters influenced by soil management have been studied as a sensitive way of predicting the long-term impacts of currently adopted agricultural practices. Microbial biomass carbon, an indicator of the amount of microbial biomass present in the soil, has been shown to be suitable for predicting the state of soil regeneration and its ability to provide nutrients and act as a regulator of soil processes. Basal respiration of the soil, expressing the activity of the microbial biomass, can quickly demonstrate stresses in the system. Soil enzymes such as β-glucosidase with its activity are highly correlated with other bioindicators and are easy to determine analytically, helping in decision making.In this way, the present work analyzes some of these parameters in soils submitted to different doses of Dolomitic limestone with the objective of evaluating the impact of this practice on the functioning of the soil microbial community.